Exposure of Lawful Values of Democratic State and Fundamentals of Fair Society - Mahmut, Utemuratov; Nizomiddin, Berdaliev; Mashkhura, Rashidova (International Journal of Psychosocial Rehabilitation, 2020)
This article analyzed the issues of improving the legal culture in society, theoretical and legal analysis of the concept of legal culture, in particular, its legal, professional, professional and professional knowledge of legal culture. analysis of theoretical types.